Continuity and change in Scandinavian police reforms - Holmberg, Lars (International journal of police science & management, 2019)
The paper provides an overview of recent police reforms in Denmark, Norway and Sweden, including what is known about the results of those reforms. The reform processes in the three countries are quite similar. The number of individual police districts is drastically reduced, strong centralized management is introduced, and reforms are expected to yield additional manpower though rationalization. To date, however, the results do not live up to expectations; reforms are hard realize in the expected time, resources are scarce, local policing is hard to maintain, and police performance and efficiency do not seem to increase. The paper offers two related explanations for the lack of results. First, all three reforms place emphasis on centralizing police management, regardless of the problems they are expected to solve. Second, a staple of Scandinavian police reforms is the quest for viability; police districts must be large enough to handle all eventualities. Even though the concept of viability has changed over the past 50 years, it is still at the core of reform plans. The paper concludes with a discussion about the possibility of ever achieving police viability.